Análise das despesas de bens e serviços de educação e do desempenho escolar - Souza, Ricardo da Silva (2015)
The object of this research is to work was analyze the spending cof individuals that consume goods and educational services, and school performance. The comparison of these two quantities was motivated by the expectations created by individuals in the acquisition of the such good in relation to the pursuit of their economic product that according Buckhan and Hannun (2001), is defined by mobility, occupational status and income. The product happens from the evolution of the individual through the gain or technical, academic and knowledge improvement, based on theories such as human capital (Schultz, 1973), market segmentation (Doering and Piore, 1971) and reproduction (Bordieu, 1978). From the empirical theories surveyed by Pinheiro and Fontoura (2007), Carvalho and Kassouf (2008), Santana and Menezes (2008), among others, which analyzed characteristics of individual or the individual’s families such as gender, color, inclusion of elderly, the and size of families that have influenced the distribution of funds for allocation of expenses and, indirectly, the expectations. In this context, a model for the evaluation of these characteristics associated with per capita income over expenditure using data from the Consumer Expenditure Survey (POF) was built. The model showed that the characteristics affect the educational spendings. The POF data about the expenditure data were compared to the data of educational performance of the tests conducted by the National Institute for Research Studies (INEP) such as Prova Brasil and ENEM, by geography region. The data for this comparsion showed similarities between five of six possible comparisons in relation to the Brazil average. These similarities may indicate in order to answers that satisfy the expectations of the individuals about educational products